KONDISI OLAHRAGA TRADISIONAL MENYIPET DAN BALOGO DI KOTA PALANGKA RAYA - Abdul Rahman Azahari (Universitas Kadiri, 2019)
The strengthening of globalization in Indonesia that brings new patterns of life and entertainment inevitably has a certain impact on the social and cultural life of the Indonesian people, including various kinds of traditional sporting activities. The theory used in this study is the concept of culture, the concept of physical education, and the sport of menyipet and balogo concept. Research use qualitative method and expected to get deep results (insight) as well as comprehensive (holistic). Like menyipet, it used to be a hunting activity to add a variety of side dishes to be consumed, besides sipet as well as a tool to defend yourself. But now, hunting is prohibited, then sipet is developed into a traditional sports arena along with balogo. As a cultural wealth in the form of traditional sports that are loaded with various noble teachings and values, the city government of Palangka Raya strives to preserve and revive the sport of menyipet and balogo through various festivals and incorporate it into the local content curriculum in high schools. The opportunity is still wide open to examine the problem of the phenomenon of traditional menyipet and balogo sports conditions in Palangka Raya.